2007
DOI: 10.1177/002214650704800406
|View full text |Cite
|
Sign up to set email alerts
|

Child Health in Peru: Importance of Regional Variation and Community Effects on Children's Height and Weight

Abstract: In developing countries, height and weight are good indicators of children's health and nutritional status. Maternal education has been accepted as one of the most important influences on child health. Using the 2000 Demographic and Health Survey of Peru, however, I find that the effect of maternal education varies as a function of region. In the most prosperous urban region, maternal education is less important for child health than in poor rural areas, and a higher level of education has a greater effect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
2
18
1
2
Order By: Relevance
“…7 Reichman et al 5 also found that prenatal care has no effects on a more direct measure of infant health—whether the child had any serious abnormal infant health condition, such as fetal alcohol syndrome, that was unlikely to be a random shock. Although studies indicate that prenatal care may improve birth outcomes in lesser-developed countries, 810 the evidence that early or adequate prenatal care improves aggregate birth outcomes in the developed world is less than compelling.…”
mentioning
confidence: 99%
“…7 Reichman et al 5 also found that prenatal care has no effects on a more direct measure of infant health—whether the child had any serious abnormal infant health condition, such as fetal alcohol syndrome, that was unlikely to be a random shock. Although studies indicate that prenatal care may improve birth outcomes in lesser-developed countries, 810 the evidence that early or adequate prenatal care improves aggregate birth outcomes in the developed world is less than compelling.…”
mentioning
confidence: 99%
“…Geographical variation in anthropometric traits has been described in many countries: Canada (Reeder et al, 1997;Shields & Tjepkema, 2006), Finland (Jokela et al, 2009), India (Dey & Debray, 2003, Peru (Shin, 2007), Poland (Hulanicka et al, 1999), Sweden (Rasmussen et al, 1999), Turkey (Iseri & Arslan, 2009), United States (Rona & Altman, 1977;Rosenbaum et al, 1985;Scarborough & Allender, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Based on an examination of the empirical literature and data availability in the 2008 GDHS, the exposure variables analyzed in this study included culture, defined by ethnicity (Bondy et al. ) and geography, defined by region of residence (Shin ).…”
Section: Methodsmentioning
confidence: 99%
“…Scholarly research shows that a large number of factors are associated with underweight prevalence among children under age five years. Based on an examination of the empirical literature and data availability in the 2008 GDHS, the exposure variables analyzed in this study included culture, defined by ethnicity (Bondy et al 2009) and geography, defined by region of residence (Shin 2007).…”
Section: Exposure Variablesmentioning
confidence: 99%